TINJAUAN HUKUM PEMILU TERHADAP MEKANISME PEMILIHAN ANGGOTA LEMBAGA DPR DI INDONESIA - Sihombing, Desi Natalia (UKM Lembaga Penalaran dan Penulisan Karya Ilmiah Fakultas Hukum Universitas Hasanuddin, 2025)
This study analyzes legal issues in legislative elections in Indonesia by highlighting three main interrelated issues, namely the crisis of meritocracy in political recruitment, high political costs, and the application of electoral thresholds. From a constitutional law perspective, elections are a constitutional instrument for realizing people's sovereignty as stipulated in Article 1 paragraph (2) of the 1945 Constitution. However, this study shows that the implementation of election regulations does not fully reflect the fundamental principles of honest, fair, open elections that provide equal opportunities as emphasized in Law Number 7 of 2017 concerning Elections. Using a normative legal approach with a statute approach, conceptual approach, and comparative approach, this study evaluates the relationship between electoral regulation design and the political behavior of actors. The analysis shows that the mechanism for recruiting legislative candidates still relies on personal loyalty and financial capacity, which contradicts the principles of meritocracy and justice in electoral law. High-cost politics also narrows political access for non-elite groups, weakens election integrity, and creates dependence on external funding. Meanwhile, the 4% electoral threshold, which aims to simplify the party system, has implications for reduced political representation and the emergence of tensions between political system efficiency and the protection of citizens' political rights. This study concludes that the combination of these three factors has shaped a procedural democracy that lacks the substance of representative democracy. These findings contribute theoretically through the integration of legal and electoral policy analysis to assess the quality of democracy in Indonesia.